2019
DOI: 10.1177/0033354919874081
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in the Dallas County Jail: Implications for Screening, Prevention, and Linkage to Care

Abstract: Objectives: Screening for hepatitis C virus (HCV) infection in jail provides an opportunity to educate and offer care to a high-risk population. We aimed to (1) estimate the prevalence of HCV infection in jail; (2) describe the demographic characteristics, risk factors, and pre-incarceration health insurance status associated with HCV infection; and (3) examine the implementation of HCV screening in jail. Methods: We conducted a retrospective analysis of an opt-out HCV screening program with HCV RNA confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…61 Implementation of reflex HCV RNA testing with antibody screening further streamlined diagnosis. 62 A comprehensive approach can couple screening with linkage to care. Drawing on a nationally recognized link to care program called transitional care coordination (TCC), 63 which provides medical case management, counseling, and comprehensive discharge planning for incarcerated people living…”
Section: Correctional Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Implementation of reflex HCV RNA testing with antibody screening further streamlined diagnosis. 62 A comprehensive approach can couple screening with linkage to care. Drawing on a nationally recognized link to care program called transitional care coordination (TCC), 63 which provides medical case management, counseling, and comprehensive discharge planning for incarcerated people living…”
Section: Correctional Populationsmentioning
confidence: 99%
“…( 59 ) Implementation of reflex HCV‐RNA testing with antibody screening further streamlined diagnosis. ( 60 )…”
Section: Innovations In Micro‐eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 1 in 3 people living with HCV infection passantibody–positive, the average age through the criminal justice system each year; people who are incarcerated are 9 times more likely than the general population to be living with HCV infection. 1,9,10 Although several studies demonstrated successful HCV testing and a high HCV antibody prevalence in the criminal justice system, 1,11-20 including studies from our own institution, 21,22 limited data exist about the incidence of HCV in criminal justice settings or which demographic subgroups are at increased risk of HCV infection.…”
mentioning
confidence: 99%
“…No guidelines exist for HCV testing in jails, where most incarcerations last less than 6 months. Increasing HCV testing in jails [ 12 ] and linking to HCV treatment on release have been shown to be feasible and effective [ 13 15 ], but only 4% of jails offer routine opt-in HCV testing [ 16 ].…”
Section: Introductionmentioning
confidence: 99%